Sexual features Among individuals with Autism Disorder and the way of Dealing with them from parents and care workers - Alkhuffash, Seham Reyad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to recognize the sexual features among individuals with autism disorder and the way of dealing with them from parents and care workers. The sample consisted of (93) children suffering from autism disorder, (51) males and (42) females. The ages of the children were between (12 years and above). The sample also consisted of (41) mothers, (15) fathers and (46) care workers. For this purpose a questionnaire of (18) items was prepared to recognize the sexual features and another questionnaire of (23) items was prepared to recognize the way of dealing with these features. Means, standard deviation, and ANOVA were computed. The results indicated that the most sexual features were” playing with genitalia in front of the family followed by confidentially. The results also showed that there were no statistically significant differences at (α=0.05) attributed to age and the degree of disability in sexual disorder. There were statistically significant differences at (α=0.05) attributed ti the variable of gender in favor of females. And about dealing with these features, the results showed that there must be special beds, training at depending on care- self through independent skills. The results indicated that dealing with sexual features came in favor of father.